2006
DOI: 10.1007/s10571-006-9008-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Therapy of Experimental Stroke

Abstract: 1. Stroke is the neurological evidence of a critical reduction of cerebral blood flow in a circumscribed part of the brain, resulting from the sudden or gradually progressing obstruction of a large brain artery. Treatment of stroke requires the solid understanding of stroke pathophysiology and involves a broad range of hemodynamic and molecular interventions. This review summarizes research that has been carried out in many laboratories over a long period of time, but the main focus will be on own experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
324
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(333 citation statements)
references
References 124 publications
6
324
1
2
Order By: Relevance
“…Inflammation can extend ischemic injury (20) to adversely affect stroke outcome (21) and may provide new therapeutic targets to treat patients outside of the narrow thrombolysis window of 3-6 h. For example, in a recent study it was shown that the administration of the drug AM-36, a Na ϩ channel blocker and an antioxidant, Histopathological analyses correspond to MPO imaging findings. (A) MPO imaging on day 3 after infarction shows a large area of enhancement in the basal ganglia and cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation can extend ischemic injury (20) to adversely affect stroke outcome (21) and may provide new therapeutic targets to treat patients outside of the narrow thrombolysis window of 3-6 h. For example, in a recent study it was shown that the administration of the drug AM-36, a Na ϩ channel blocker and an antioxidant, Histopathological analyses correspond to MPO imaging findings. (A) MPO imaging on day 3 after infarction shows a large area of enhancement in the basal ganglia and cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms affecting nonvascular genes contributing to stroke severity, such as proteins involved in pathways affecting sensitivity of neurons and glia to hypoxia and apoptosis, distal thrombosis/lysis, reperfusion injury, and endogenous neuroprotective mechanisms, also likely contribute to variation in infarct volume (Hossmann, 2006). To estimate the relative contribution of genetic variation in vascular determinants of infarct volume, we assembled MCA territory plus collateral number and diameter into a deterministic 'equation' ( Figure 4A).…”
Section: Infarct Volume Strongly Correlates With the Extent Of The Namentioning
confidence: 99%
“…Heubner (1874) described the presence of similar collaterals, which he termed 'leptomeningeal anastomoses,' interconnecting some of the outer branches of the anterior (ACA), middle (MCA), and posterior cerebral artery (PCA) trees of the pial circulation supplying the human cerebral cortex. Perfusion of the penumbral cortex after proximal obstruction of an artery (e.g., the MCA) distal to the Circle of Willis is assumed to depend, in part, on the extent (i.e., number and diameter) of these preexisting vessels (Brozici et al, 2003;Liebeskind, 2005;Hossmann, 2006). However, whether the pial collateral circulation significantly impacts infarct volume is a controversial subject that has received relatively little treatment in recent authoritative monographs and textbooks (Brozici et al, 2003;Mohr et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombolytic therapy (eg, recombinant tissue plasminogen activator) to achieve early arterial recanalization is the only option currently available to treat ischemic stroke. But this therapy's time-dependent effect (within 3 h after the event) limits its clinical use to only 5% of candidate patients (1), and it carries an increased risk of intracranial hemorrhage, reperfusion injury, and diminishing cerebral artery reactivity (2)(3)(4)(5). Neuronal death and injury after cerebral ischemia involve pathological changes associated with necrosis and delayed apoptosis (6,7).…”
mentioning
confidence: 99%